2007
DOI: 10.1590/s0103-50532007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of the sample decomposition of green and roasted coffee for determination of nutrients and data exploratory analysis

Abstract: Os teores de vários nutrientes foram determinados em 35 amostras de cafés verdes e torrados, por espectrometria de absorção atômica em chama (Ca, Mg, Fe, Cu, Mn e Zn), fotometria de emissão atômica em chama (Na e K) e pelo método Kjeldahl (N) após preparação das amostras por dois procedimentos de decomposição via úmida: i) sistema aberto (bloco digestor) e ii) sistema fechado (forno de microondas convencional com controle de pressão e temperatura). A exatidão dos procedimentos foi verificada analisando-se três… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Each sample of 250 mg was digested using 7.0 mL of concentrated HNO 3 and 1.0 mL of 30% (w/w) H 2 O 2 . [ 3,34–37 ] The microwave oven program used to digest the coffee samples is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Each sample of 250 mg was digested using 7.0 mL of concentrated HNO 3 and 1.0 mL of 30% (w/w) H 2 O 2 . [ 3,34–37 ] The microwave oven program used to digest the coffee samples is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Welna et al (2013) noted that the transfer of PTEs into brew might vary probably related to coffee type (instant and ground coffees). Amorim Filho et al (2007) also observed that the concentration of Fe and Cr is highest in steel grinders because of releasing these metals into the coffee samples via the mill overheating. Additionally, Nędzarek et al (2013) reported that potential contamination with PTEs may originate from packaging materials containing metals during coffee storage.…”
Section: Concentration Of Pbmentioning
confidence: 99%
“…In the case of the brewing method, it is reported that the extraction levels of most PTEs are highest in the Turkish coffee method, in which coffee is boiled together with water (Nędzarek et al 2013;Şemen et al 2017). Regarding the type of coffee in terms of raw or roasted, it is noteworthy that the concentrations of PTEs in green coffee are typically lower than those determined in roasted coffees, probably due to removing water and volatile constituents (Amorim Filho et al 2007;da Silva et al 2017). Moreover, Şemen et al (2017) concluded that studied PTEs are leached to the infusion more difficult from roasted coffee than from green coffee.…”
Section: Concentration Of Pbmentioning
confidence: 99%
“…0.13-0.17 0.14-0.17 0.15-0.17 0.14-0.17 Tables 2 and 3 show that the concentration of analytes (major and trace elements) exhibited different orders of magnitude. Therefore, data were autoscaled before HCA and PCA in order to achieve independence on the factors of different scale of the element concentrations, in order to for all the factors to have the same importance (Amorim Filho et al 2007;Anunciação et al 2011).…”
Section: Analysis Of Samplesmentioning
confidence: 99%